2015
DOI: 10.1111/1541-4337.12133
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Hazards in Irrigation Water: Standards, Norms, and Testing to Manage Use of Water in Fresh Produce Primary Production

Abstract: Accessibility to abundant sources of high-quality water is integral to the production of safe and wholesome fresh produce. However, access to safe water is becoming increasingly difficult in many parts of the world, and this can lead to the production of fresh produce contaminated with pathogenic microorganisms, resulting in increased risk of human disease. Water, an important raw material in the fresh produce chain, is used in considerable amounts in many operations, including irrigation and application of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
172
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(184 citation statements)
references
References 151 publications
6
172
0
6
Order By: Relevance
“…Sources of water used for irrigation can include rain, ground, surface, and wastewater (Gelting et al, ; Ijabadeniyi, Debusho, Van der Linde, & Buya, ). Presence of pathogens in these water sources has recently attracted attention (Uyttendaele et al, ) due to the associated disease outbreaks linking contaminated water with fresh produce (Gelting et al, ). Irrigation water contaminated with animal feces and human waste is considered one possible route of preharvest vegetable contamination (Olaimat & Holley, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sources of water used for irrigation can include rain, ground, surface, and wastewater (Gelting et al, ; Ijabadeniyi, Debusho, Van der Linde, & Buya, ). Presence of pathogens in these water sources has recently attracted attention (Uyttendaele et al, ) due to the associated disease outbreaks linking contaminated water with fresh produce (Gelting et al, ). Irrigation water contaminated with animal feces and human waste is considered one possible route of preharvest vegetable contamination (Olaimat & Holley, ).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding this gap in knowledge, irrigation water has long been regarded as an important vehicle for pathogens associated with foodborne illnesses (Uyttendaele et al, 2015). According to the Centers for Disease Control and Prevention, outbreaks that occurred during 2013 to 2014 from drinking water systems solely supplied by surface water accounted for nearly 80% of reported cases (Allende and Monaghan, 2015; Benedict et al, 2017; Uyttendaele et al, 2015). However, there is a paucity of research capable of linking microbial contamination in irrigation water to foodborne outbreaks in the United States (Pachepsky et al, 2016; Partyka et al, 2018).…”
mentioning
confidence: 99%
“…A review of risks posed by food of nonanimal origin revealed that the main hazards to consider in leafy salads are Salmonella and norovirus (10). Uyttendaele et al (36) identified E. coli O157, Salmonella, norovirus, and Cyclospora cayetanensis as the main causes FIOs associated with leafy salad. In these cases, the most probable route of contamination (i.e., risk factor) of the produce was through direct or indirect fecal contamination from infected livestock or workers.…”
Section: Developing An Evidence-based Gra For Primary Producersmentioning
confidence: 99%
“…Alternatively, the grower could monitor irrigated soil for indicator species, investigate use of a relatively safer water source, avoid the use of uncontrolled surface water, or treat the water (1,36). This last option is presented in scenario 2.…”
Section: Scenariosmentioning
confidence: 99%